Instruments for Measuring the Resilience of Indigenous Adolescents: An Exploratory Review - Jongen, Crystal; Langham, Erika; Bainbridge, Roxanne; McCalman, Janya (Frontiers in Public Health, 2019)
Introduction: Resilience is enabled by internal, individual assets as well as the resources available in a person's environment to support healthy development. For Indigenous people, these resources and assets can include those which enhance cultural resilience. Measurement instruments which capture these core resilience constructs are needed, yet there is a lack of evidence about which instruments are most appropriate and valid for use with Indigenous adolescents. The current study reviews instruments which have been used to measure the resilience of Indigenous adolescents in Canada, Australia, New Zealand, and the United States (the CANZUS nations). The aim is to provide guidance for the future use of instruments to measure resilience among Indigenous adolescents and provide recommendations for research to strengthen evidence in this area. Method: Instruments were identified through a systematic search of resilience intervention and indicator studies targeting Indigenous youth from CANZUS nations. The studies were analyzed for information on the constructs of resilience measured in the instruments, their use with the targeted groups, and their psychometric properties. A second search was conducted to fill in any gaps in information. Instruments were included if they measured at least one construct of resilience reflecting individual assets, environmental resources, and/or cultural resilience. Results: A total of 20 instruments were identified that measured constructs of resilience and had been administered to Indigenous adolescents in the CANZUS nations. Instruments which measured both individual assets and environmental resources (n = 7), or only environmental resources (n = 6) were most common. Several instruments (n = 5) also measured constructs of cultural resilience, and two instruments included items addressing all three constructs of individual assets, environmental resources, and cultural resilience. The majority of the reviewed studies tested the reliability (75%) and content or face validity (80%) of instruments with the target population. Conclusion: There are several validated instruments available to appropriately measure constructs of resilience with Indigenous adolescents from CANZUS nations. Further work is needed on developing a consistent framework of resilience constructs to guide research efforts. Future instrument development and testing ought to focus on measures which include elements of all three core constructs critical to Indigenous adolescent resilience.